Factor Structure and Measurement Invariance of the Coimbra Neuropsychological Assessment Battery (BANC). (25th May 2017) - Moura, Octávio; Albuquerque, Cristina P; Salomé Pinho, Maria; Vilar, Manuela; Filipa Lopes, Ana; Alberto, Isabel; Pereira, Marcelino; Santos, Maria João Seabra; Simões, Mário R
Abstract: Objective: This study aimed to investigate the factor structure of the Coimbra Neuropsychological Assessment Battery (BANC), which is an individually administered battery designed to assess a wide range of neurocognitive functions in children. Method: Using the standardization sample of the BANC, a confirmatory factor analysis and a multiple-group analysis were conducted to examine the factor structure and the measurement invariance of three main domains (Memory, Language, and Attention/Executive Functions) in 833 children aged 7–15 years. Results: Consistent with the BANC's conceptualization, the three-correlated-factor model demonstrated the most adequate fit to the data. The measurement invariance of the three-correlated-factor model across two age-groups (7–9 years and 10–15 years) was supported (configural, metric, and partial scalar invariance). Conclusion: Overall, the BANC shows adequate psychometric properties and provides useful information regarding the children's neuropsychological functioning.